Development Strategy of Sustainable Aviation Fuel - Lijun Tian; Xin Liu; Jixing Lyu; Xiaojun Yang; Changjiang You; Xuegong Chen (中国工程科学)
The sustainable aviation fuel (SAF) has three value attributes: environmental protection, energy transformation, and industrial layout optimization, and it is a key development area for aviation environmental governance internationally. China's SAF industry started relatively late, lacks independent technologies, and has an immature business model. It is currently in a critical period of transitioning from industrial demonstration to commercial application. Therefore, exploring the independent development of the SAF industry is crucial for promoting the green development of the civil aviation industry. This study identifies the various elements and their inherent connections that contribute to the development of the SAF industry and elucidates the environmental, energy, and economic values of the industry. Moreover, it sorts out the development pattern of the international SAF industry from two aspects: policy support and technological development progress, and summarizes the scale and mode, technology and cost, and policy mechanism of China's SAF industry. Furthermore, the study clarifies the development ideas and technology application plans of the industry and proposes the following development suggestions: (1) issuing industry regulatory frameworks to improve industry standards and norms, (2) increasing financial support by expanding tax incentives, and (3) strengthening technological innovation while exploring new business models. The study is expected to provide references for the implementation of the carbon peaking and carbon neutralization goals in China's civil aviation industry, as well as for the planning, technology research and development, and commercial application of the SAF industry, thereby promoting the sustainable development of the SAF industry.